2016
DOI: 10.2147/copd.s114802
|View full text |Cite
|
Sign up to set email alerts
|

Association between adherence to medications for COPD and medications for other chronic conditions in COPD patients

Abstract: BackgroundPatients with COPD often have multiple comorbidities requiring use of multiple medications, and adherence rates for maintenance COPD (mCOPD) medications are already known to be suboptimal. Presence of comorbidities in COPD patients, and use of medications used to treat those comorbidities (non-COPD medications), may have an adverse impact on adherence to mCOPD medications.ObjectiveThe objective of the study was to evaluate the association between non-adherence to mCOPD medications and non-COPD medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
2
24
4
2
Order By: Relevance
“…[ 26 ] Furthermore, multivariate analysis failed to find significant association between nonadherence and comorbidities. This is inconsistent with previous studies[ 24 27 28 ] that have suggested that comorbidities are one of the greatest barriers to achieve medication adherence.…”
Section: Discussioncontrasting
confidence: 92%
“…[ 26 ] Furthermore, multivariate analysis failed to find significant association between nonadherence and comorbidities. This is inconsistent with previous studies[ 24 27 28 ] that have suggested that comorbidities are one of the greatest barriers to achieve medication adherence.…”
Section: Discussioncontrasting
confidence: 92%
“…Problems with medication adherence among patients with COPD have been well documented worldwide 3539. Dhamane et al, using a large administrative claims database (N=14,117; mean age, 69.9 years), observed that 79.2% of patients were nonadherent to maintenance COPD medications with a mean PDC of 0.47 40. In another recent large retrospective cohort study based on claims data provided by a German statutory health insurance fund (N=45,937), and Mueller et al, it was reported that approximately two-thirds of patients with COPD failed to continue treatment after 12 months 41.…”
Section: Discussionmentioning
confidence: 99%
“…Low expectation of the medication, presence of comorbid illnesses, depressed mood, increased age, current smoking, and lack of confidence in the provider are the most consistent independent predictors of low adherence [204]. Adherence to medications may be impacted by factors that do not change regardless of disease or medication type but reasonably is influenced by aspects of patient-related considerations (forgetfulness, suboptimal health knowledge, etc.…”
Section: Proceedingsmentioning
confidence: 99%